Determinant of Accounting Learning Achievement: Case Study of Accounting Program Students Politeknik Negeri Madiun: Penentu Prestasi Belajar Akuntansi: Studi Kasus Mahasiswa Program Akuntansi Politeknik Negeri Madiun - Amrulloh, Amri; Amalia Dini, Intan (Tinta Emas Publisher, 2023)
Research conducted by the author aims to determine how much influence the interest in learning, learning motivation, learning discipline and family environment on accounting learning achievement. This research is expected to provide a fundamental knowledge for educational institutions in order to improve accounting learning achievement. The population and sample used were for students in the accounting study program at the Politeknik Negeri Madiun. Many of the samples used for the purposes of this study were 69 students in accounting study programs. This research uses primary data which contains statements in the form of questionnaires which are measured using a liquid scale. The statistical method used to test this hypothesis uses multiple linear regression analysis. The results of this study indicate that interest in learning, learning motivation, learning discipline and family environment have a significant effect on accounting learning achievement